Preparation of silver nanoparticle-containing ceramic filter by in-situ reduction and application for water disinfection. Issue 3 (June 2019) - Ngoc Dung, Tran Thi; Phan Thi, Lan-Anh; Nam, Vu Nang; Nhan, Tran Thi; Quang, Dang Viet
Graphical abstract: Highlights: Silver nanoparticles (SNPs) in ceramic filter were synthesized by in-situ reduction. Activated carbon was used as active filler for the silver reduction. The filter shows a great antibacterial efficiency and low Ag release. Antibacterial activity was sustained for a long period. Abstract: Silver nanoparticle (SNP)-containing ceramic filter (SNP-CF) has been widely investigated for water disinfection but the filters usually lose their antibacterial efficacy after short time because of silver leaching. In this study, the SNP-CF has been successfully prepared by an in-situ reduction method in which silver nitrate was first impregnated into activated carbon, which was then added into ceramic mixture for filter production. Silver nitrate in activated carbon got reduced to metallic silver by thermal treatment. Resulting filters were characterized by various techniques including saturated water method, nitrogen adsorption/desorption, scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. The utilization of activated carbon as filler produced ceramic filter with high porosity (64%) compared to charcoal (56%) and sawdust (29%), particularly, the porosity of activated carbon ceramic filter was not affected by the addition of SNPs. The SNP-CF having mesopores with pore diameter from 2 to 6 nm and pore volume of 0.02 cm 3 /g. The SNPs uniformly distributed throughout ceramic structure helps the filter constantly release silver for a long period. Silver concentrations detected in filtrate were 0.04 ppm for SNP-CF prepared by in-situ reduction (0.03 wt% silver) and 0.736 ppm for SNP-coated ceramic filter (0.03 wt% silver). The filter showed a great antibacterial activity with 100% of E. coli and coliform eliminated via filtration for extended period (10 weeks). The success of this work has proposed a novel and facile method to prepare SNP-CF that can be applied for water disinfection.